1997
DOI: 10.1016/s1010-7940(97)00275-3
|View full text |Cite
|
Sign up to set email alerts
|

The impact of delayed diagnosis of lung cancer on the stage at the time of operation

Abstract: A few months delay before final treatment of a non-small-cell lung cancer seems to have an impact on the perioperative stage of the cancer, and thereby on the patients prognosis. A screening of asymptomatic risk-group patients will result in recognition of early lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
3
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(87 citation statements)
references
References 12 publications
4
76
3
3
Order By: Relevance
“…In the work by Billing & Wells (7), total delay was de ned as the time from the rst visit to the general practitioner until surgery, and then further divided into 11 subgroups in order to determine the reasons for the observed delay (see Table 1). In the work by Christensen et al (8), the endpoint was date of operation or the date when it was decided that surgery was not indicated. These are all relevant clinical endpoints, but they are not comparable, as some time must elapse between the decision to operate and the time surgery is actually performed.…”
Section: Doctors' Delaymentioning
confidence: 99%
See 1 more Smart Citation
“…In the work by Billing & Wells (7), total delay was de ned as the time from the rst visit to the general practitioner until surgery, and then further divided into 11 subgroups in order to determine the reasons for the observed delay (see Table 1). In the work by Christensen et al (8), the endpoint was date of operation or the date when it was decided that surgery was not indicated. These are all relevant clinical endpoints, but they are not comparable, as some time must elapse between the decision to operate and the time surgery is actually performed.…”
Section: Doctors' Delaymentioning
confidence: 99%
“…Only one of the studies focused on the association between delay and survival, and for a group of cancer patients, not analysed separately for lung cancer, a signi cantly better rate of survival was found for patients having patient delay than for patients having doctors' delay (10). One study found a signi cantly longer delay for stage III, IV than for stage I, II disease at the pre-hospital, but not at the in-hospital level (8). In another study 6 out of 29 patients became clinically incurable while waiting (9).…”
Section: The Prognostic Impact Of Delaymentioning
confidence: 99%
“…However, diagnostic and treatment delays continue to remain very common problems among the patients with lung cancer (5)(6)(7)(8). Some studies looking at the impact of delays on tumour stage and survival rate have shown that delays affected tumour stage and survival rate (9)(10)(11). On the other hand, others have reported that delays were not associated with tumour stage and survival rate (5,7,8,12).…”
Section: Introductionmentioning
confidence: 99%
“…Resultado semelhante foi referido por outros autores, que não encontraram associação entre retardo no diagnóstico ou tratamento e estádio tumoral ou sobrevida dos pacientes. (10,12,15,29) Contrastando com esses dados, Christensen et al, (13) em um estudo dinamarquês incluindo 172 pacientes com câncer de pulmão, relataram ser o tempo entre o aparecimento dos sintomas e a cirurgia, e entre o primeiro contato com o sistema de saúde e a cirurgia menor nos pacientes com melhor prognóstico (estádios I e II). Em outro estudo, seis de 29 pacientes tornaram-se clinicamente incuráveis enquanto aguardavam radioterapia.…”
Section: Discussionunclassified
“…Diversos estudos avaliaram o tempo gasto para investigação e tratamento do câncer de pulmão e detectaram retardo excessivo, tanto relacionado ao paciente (5)(6)(7)(8)(9)(10)(11) quanto ao sistema de saúde no qual o paciente foi atendido. (12)(13)(14)(15)(16)(17) Segundo o Standing Medical Advisory Committee da Inglaterra, o tempo de investigação até a ressecção do tumor não deveria ultrapassar seis a oito semanas. (18) Entretanto, o impacto do tempo despendido até o início do tratamento do câncer de pulmão na sobrevida dos pacientes continua sendo discutido.…”
Section: Retardo No Diagnóstico E No Tratamento Cirúrgico Do Câncer Dunclassified